FORMULATION OF EMULGEL CONTAINING ROBUSTA GREEN COFFEE (COFFEA CANAPHORA) EXTRACT: FORMULATION OF EMULGEL CONTAINING ROBUSTA GREEN COFFEE (COFFEA CANAPHORA) EXTRACT - Feronika Evma Rahayu; Inggiet Fitria Kusnawardhani (Journal of Research in Pharmacy and Pharmaceutical Sciences, 2024)
Robusta green coffee (Coffea canephora) contains chlorogenic acid compounds, caffeine, carbohydrates, fats, amino acids, volatile compounds, and minerals. Robusta green coffee extract is formulated in the form of emulgel as a topical application because of the potential for chlorogenic acid to improve dry skin diseases. The purpose of this study was to formulate an extract of robusta green coffee (Coffea canephora) in the form of an emulgel and to determine the physical characteristics and stability of the emulgel. The research design used is the experimental method. This research begins with the extraction of robusta green coffee using the maceration method, phytochemical screening, and the manufacture of emulgel preparations with variations in the ratio of emulsion and gel, namely F0 (1:6), F1 (1:6), F2 (3:6), and F3 (6:6). The process of making emulgel is making emulsion, making gel, and incorporating emulsion into gel. The evaluation carried out on the emulgel preparation included physical examination, determination of pH, emulsion type test, viscosity test, centrifugation test, and freeze and thaw test. The results of the physical characteristics of the emulgel preparation were good and met the requirements based on the parameters of physical examination, determination of pH, and emulsion type test and stable emulgel preparation in freeze thaw stability testing based on parameters of physical examination, determination of pH, emulsion type test, and centrifugation test. Analysis of chlorogenic acid levels in emulgel preparations using UV-Vis spectrophotometer. The levels of chlorogenic acid in the emulgel preparations did not contain chlorogenic acid (F0), 76.70% (F1), 82.77% (F2), and 79.64% (F3).